Factors related to work accidents among construction workers - Fristiyan Ahmad Dauly (International Journal of Nursing and Midwifery Research, 2022)
Accidents are unexpected events and it is not expected that in the event there is no element of premeditation, even more so in the form of planning. Accidents can inhibit project development, material losses, lost time, disability which can reduce the quality of life for workers and even death. Based on PT. PP (Persero) Tiffani Apartment Project, Kemang, South Jakarta, evaluating accidents form in April- September 2010, obtained 22 cases of work accidents than 96 construction workers. Statistical test using Chi Square to see the relationship between two variables. That is the variable age, years of work units and long working hours associated with workplace accidents on construction workers. The results showed that construction workers who suffered work accidents as many as 21 people (35%) and construction workers who did not suffer work accidents as many as 39 people (65%). From the results of statistical tests, variables related to the accident were age (p value = 0.003), years of work (p value = 0.007) and longer working hours (p value = 0.000). To reduce the number of accidents that occur on construction workers by training the young-old construction workers and increase the frequency of occupational health and safety training, to supervise a higher priority to the construction workers who are younger than 29 years, providing adequate rest periods for construction workers who work more than the normal working hours, making the work shift, giving rewards and punishments to the construction workers,